Transcendentalism and the cultivation of the soul - Andrews, Barry Maxwell (Amherst : University of Massachusetts Press, 2017)
American Transcendentalism is often seen as a literary movement--a flowering of works written by New England intellectuals who retreated from society and lived in nature. In Transcendentalism and the Cultivation of the Soul, Barry M. Andrews focuses on a neglected aspect of this well-known group, showing how American Transcendentalists developed rich spiritual practices to nurture their souls and discover the divine. The practices are common and simple -- among them, keeping journals, contemplation, walking, reading, simple living, and conversation. In approachable and accessible prose, Andrews demonstrates how Transcendentalism's main thinkers, Emerson, Thoreau, Fuller, and others, pursued rich and rewarding spiritual lives that inspired them to fight for abolition, women's rights, and education reform. In detailing these everyday acts, Andrews uncovers a wealth of spiritual practices that could be particularly valuable today, to spiritual seekers and religious liberals. -- Provided by publisher.
The soul of the age -- The transcendentalist crisis of faith -- Transcendentalist spirituality -- The art of life -- Three prerequisites of the spiritual life -- Solitude, contemplation, sauntering, and simple living -- Reading, conversation, and journal writing -- Religious cosmopolitanism -- Self-culture and social change -- Abolition and women's rights -- Education, environmentalism, and sustainability -- Church reform and the free religious association -- The legacy of transcendentalism.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 072
Keywords: Transcendentalism (New England); Social movements; Spiritual life; Spirituality; Social movements; Spiritual life; Spirituality; Transcendentalism (New England); PHILOSOPHY / Movements / Idealism; RELIGION / General; Electronic books